Recent advances and new horizons in zeolite science and technology - Chon, H. (Hakze); Woo, Seong Ihl.; Park, S.-E. (Sang-Eon); ScienceDirect eBooks; International Zeolite Conference 1996 : Taejŏn-si, Korea) (Amsterdam ; New York : Elsevier, 1996)
This volume was conceived as a handbook for the Pre-Conference Summer School on Zeolites, held in Taejon, Korea. The 11th IZC Summer School was organized to acquaint those already actively working in zeolite science and technology with the latest developments and to develop new prospects of zeolite science and technology for the 21st century. The aim of this volume is to give an extensive review and analysis of the important new findings of the last 10 years on the synthesis, characterization and applications of zeolite materials as well as the prediction of new R & D directions for the next decade.
Cover -- Contents -- Preface -- List of contributors -- Chapter 1. Periodic Mesoporous Materials: Synthesis, Characterization and Potential Applications -- Introduction -- Synthesis and characterization of M41S and related materials 2 -- Catalytic Applications of M41S and related materials -- Other potential applications -- Concluding remarks -- References -- Chapter 2. Synthesis, Characterization, and Catalysis with Microporous Ferrierites, Octahedral Molecular Sieves, and Layered Materials -- Overview -- n-Butene isomerization with boron substituted zeolites and ferrierites -- Synthesis of octahedral molecular sieves and octahedral layered materials -- Characterization of octahedral molecular sieves and octahedral layered materials -- Catalytic activity of octahedral molecular sieves and octahedral layered systems -- References -- Chapter 3. Organic Zeolites? -- Introduction -- Dianin's Compound -- Helical tubulates of 2,6-Dimethylbicyclo[3.3.1]nonane-exo-2,exo-6-diol -- [Ag(1,3,5-tris(3-ethynylbenzonitrile)benzene)CF3SO3]-2C6H6 -- [Ag(1,3,5-tris(4-thynylbenzonitrile)benzene)CF3SO3]-2C6H6 -- Further Directions -- References and Notes -- Chapter 4. Spectroscopic Characterisation of Zeolites -- Introduction -- EPR spectroscopy -- Infrared spectroscopy -- Raman spectroscopy -- UV-Visible spectroscopy -- X-ray absorption spectroscopy -- Mass spectrometry of zeolites -- References -- Chapter 5. Characterization of Zeolitic Materials by Solid-State NMR-State of the Art -- Introduction -- High resolution solid state NMR spectroscopy-experimental techniques including 2D NMR -- Recent highlights about the framework characterization -- Pore architecture investigated by NMR -- In-situ NMR studies with zeolitic materials -- Diffusion of adsorbed molecules monitored by NMR -- Acidity of zeolitic materials -- Concluding remarks -- References -- Chapter 6. Application of Surface Science Techniques in the Field of Zeolitic Materials -- Introduction -- Photoelectron spectroscopy (XPS) and other surface analysis -- XPS of zeolites -- Acidity in zeolites -- Basicity in zeolites -- Active centers in zeolitic oxidation catalysts -- Conclusion -- References -- Chapter 7. Computational Approaches in Zeolite Structural Chemistry -- Roles of simulation -- Structural characterization -- Occluded or sorbed molecules and clusters -- Meso- and macro-structure -- Dynamical behavior -- Sorptive behavior -- Intrazeolite chemistry -- Some five year challenge areas -- Conclusion -- References -- Chapter 8. What Can Be in the Channels and Cavities of Zeolites? -- Zeolites and their frameworks -- The contents of neutral zeolite frameworks -- The contents of charged zeolite frameworks -- Molecular and ionic sieving -- Sorption of atoms and molecules -- A single substance may react within a zeolite -- Two different substances may react within a zeolite Encapsulation -- An empty zeolite is a crystalline solvent -- An appeal for care in the preparation of samples for study -- Final comments -- References -- Chapter 9. Conjugated and Conducting Nanostructur.
Papers presented at the 11th International Zeolite Conference held in 1996 at Taejon, Korea.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Zeolites -- Congresses; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; SCIENCE -- Chemistry -- Industrial & Technical; Zeolites; Zeolites; Electronic books